1997
DOI: 10.5254/1.3538461
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Elastomeric Blends of Nylon-6/Acrylate Rubber: Influence of Interaction on Mechanical and Dynamic Mechanical Thermal Properties

Abstract: Nylon-6 and acrylate rubber (ACM) were melt blended in a Brabender Plasticorder at 220 °C and 40 rpm rotor speed. The reactive nature of the blend is reflected in the mixing torque behavior of the blends at different compositions. The solubility characteristics of the blends in formic acid solution gives an approximate idea of the amount of nylon-6 grafted onto ACM and vice-versa. A reaction mechanism is proposed based on the well known epoxy—amine and epoxy—acid reactions and is confirmed by infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 2 publications
0
45
0
Order By: Relevance
“…Apart from the above two, a secondary rubber transition is also found at higher temperature side (in the region between 15-25°C), which is associated with the restricted relaxation of ACM chains grafted to the nylon-6 matrix. 9 As discussed earlier, during the melt-blending operation in Brabender Plasticorder in the temperature range of 220 -235°C, nylon-6 reacts with ACM to form graft copolymers at the interfacial region. The flexibility of the ACM rubber chains when grafted to the plastic matrix is believed to be greatly reduced relative to that of the chains in the bulk polymer, with the mobility increasing gradually with increasing distance from the boundary.…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the above two, a secondary rubber transition is also found at higher temperature side (in the region between 15-25°C), which is associated with the restricted relaxation of ACM chains grafted to the nylon-6 matrix. 9 As discussed earlier, during the melt-blending operation in Brabender Plasticorder in the temperature range of 220 -235°C, nylon-6 reacts with ACM to form graft copolymers at the interfacial region. The flexibility of the ACM rubber chains when grafted to the plastic matrix is believed to be greatly reduced relative to that of the chains in the bulk polymer, with the mobility increasing gradually with increasing distance from the boundary.…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
“…The very reactive nature of the blend components is evident from the figure, which is manifested in the rise of mixing torque after the initial softening period. It was concluded with the help of infrared (IR) and nuclear magnetic resonance (NMR) 9 earlier that during meltblending operation in Brabender Plasticorder at the temperature range of 220 -235°C, nylon-6 and ACM chemically interact with each other. The amine and carboxyl acid end groups of nylon-6 react with the reactive epoxy groups (which are present as cure sites) of ACM to form high-molecular-weight graft copolymers, which increase the viscosity of the mixture and, hence, raise the mixing torque.…”
Section: Mixing Torque Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the existence of a high interfacial tension between the two polymers. Bhowmick et al [16][17][18][19][20][21][22][23][24] also reported various TPEs and TPVs. Recently Naskar et al [25][26][27][28][29][30] extensively studied the effect of various peroxides including multifunctional peroxides as crosslinking agents in PP/EPDM TPVs.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported preparation and properties of a large number of thermoplastic elastomeric rubber-plastic blends. [27][28][29][30] In the present work, two different TPEs have been prepared from rubber-plastic blends. One of them has been made of completely saturated, nonpolar rubber and plastic viz.…”
Section: Introductionmentioning
confidence: 99%